The Anterolateral Thigh Flap for Lower Extremity Reconstruction - Landuyt, Koenraad Van (Thieme Medical Publishers, 2006)
The anterolateral thigh flap can be considered to be one of the workhorses of perforator flaps. Its ease of dissection together with the long and reliable pedicle make it extremely suitable as a free-skin flap. The versatility of the flap allows for multiple skin islands on one pedicle, “chimeric” type of flaps, and proximally and distally based local pedicled flaps as well. However, especially in the Caucasian patient, the flap can be rather thick, and the donor-site morbidity is not always accepted, which limits somewhat its popularity in lower extremity reconstruction, though in selected cases it proves to be an extremely useful adjunct to our reconstructive possibilities of the lower leg.